UNDERSTANDING MOTIVATION LOSS AND BEHAVIORAL DISENGAGEMENT OF TERTIARY STUDENTS IN FLEXIBLE LEARNING: A SELF-DETERMINATION THEORY PERSPECTIVE (Malaysian Journal of Learning and Instruction, 2024)
Purpose – Flexible learning is a delivery modality associated with positive outcomes, but its use at the height of the COVID-19 pandemic has been associated with dark student experiences, such as poor interest and dishonesty among students. To understand how and why many tertiary students lost their motivation and became disengaged in pandemic-era flexible learning, this qualitative research was designed.Methodology – A total of 27 tertiary students in five separate groups volunteered to be interviewed. A focus group discussion protocol was developed based on the propositions of Self-Determination Theory (SDT) and this protocol produced about eight hours of narrative data in audio form. The researcher performed thematic analysis to make sense of the transcriptions of the data, and the initial codes and themes were subjected to an external audit for purposes of methodological integrity.Findings – Eight need-thwarting behaviors of key social agents emerged, such as instructors’ rigid and negligent behaviors, peers’indifferent and selfish behaviors, and burdensome behaviors of people at home. These behaviors were tied to participants’ cognitiveappraisals of psychological need frustration that emerged in eight themes, which comprised having problems balancing school and home obligations, believing that outputs were misevaluated, and feelings of disconnection from peers. These appraisals could be related to seven themes of motivation and engagement issues reported by participants, notably amotivation, poor concentration, low effort, and dishonesty.Significance – The findings highlight the importance of addressing these need frustrations in order to improve tertiary students’ motivation and engagement in academic tasks delivered through flexible learning in higher education.